Pengembangan Metode Komunikatif dengan Teori Belajar Gagne Untuk Keterampilan Berbicara Bahasa Arab Siswa - Fadilah, Fitri Nurul; Zukhaira, Zukhaira (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
This research is motivated by problems in learning students' Arabic speaking skills. The learning methods used need to be more appropriate. Therefore, it is necessary to develop a learning method that can motivate, and add to student practice, one of which is by developing communicative methods so that students practice frequently and combining it with Gagne's learning theory which pays attention to the learning phases so students are motivated. The research design used the ADDIE model. The results of this study proved that students and teachers need methods that can increase students' motivation and courage and familiarize students with practicing communication. Prototypes of learning methods are recorded and arranged like lesson plans based on the 2013 and independent curriculum. The assessment results of method experts, linguists, and teachers as practitioners for the development of the method obtained a total score of 363, included in category with a very good predicate.